2021
DOI: 10.1111/add.15501
|View full text |Cite
|
Sign up to set email alerts
|

All‐cause and suicide mortality among people with methamphetamine use disorder: a nation‐wide cohort study in Taiwan

Abstract: Background and aims Although methamphetamine use is a serious public health problem, large‐scale cohort studies assessing methamphetamine‐related mortality are scant. This study investigated all‐cause mortality and suicide methods in people with methamphetamine use disorder. Design A cohort record‐linkage study using data from Taiwan's National Health Research Institute Database (NHIRD) linked to Taiwan's National Death Certification System. Setting Taiwan. Participants A total of 23 248 individuals with metha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Nevertheless, studies from 2001 onwards in Hong Kong suggested that males were more likely to adopt charcoal burning in Hong Kong (Chan et al, 2005;Chang et al, 2019). This concurs with findings from Canada, Mainland China, Taiwan, Japan and South Korea (Chang et al, 2010(Chang et al, , 2016Chen et al, 2012aChen et al, , 2014Cheng et al, 2015;Choi et al, 2014;Han et al, 2018;Ji et al, 2014;Kamizato et al, 2009;Lee et al, 2014aLee et al, , 2014bLee et al, , 2021Pan et al, 2010;Sinyor et al, 2019;Yoshioka et al, 2014Yoshioka et al, , 2016.…”
Section: Risk Factorssupporting
confidence: 56%
“…Nevertheless, studies from 2001 onwards in Hong Kong suggested that males were more likely to adopt charcoal burning in Hong Kong (Chan et al, 2005;Chang et al, 2019). This concurs with findings from Canada, Mainland China, Taiwan, Japan and South Korea (Chang et al, 2010(Chang et al, , 2016Chen et al, 2012aChen et al, , 2014Cheng et al, 2015;Choi et al, 2014;Han et al, 2018;Ji et al, 2014;Kamizato et al, 2009;Lee et al, 2014aLee et al, , 2014bLee et al, , 2021Pan et al, 2010;Sinyor et al, 2019;Yoshioka et al, 2014Yoshioka et al, , 2016.…”
Section: Risk Factorssupporting
confidence: 56%
“…28 The standardized mortality ratio (SMR) was estimated as the ratio of observed mortality in the bipolar disorder cohort to expected deaths in the general population of Taiwan between February 1, 2001, and December 31, 2016, as described in a previous study. 29 In brief, the expected number of deaths was estimated by sex-specific mean mortality rates in each 10-year age interval of the Taiwanese general population in a corresponding year multiplied by the contributed person-years in the at-risk period experienced by individuals with bipolar disorder in each age and sex category. The value for each age and sex group was then summed to obtain the total number of expected deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the magnitudes of possible treatment effects may be stronger for patients with alcohol use disorder than for the other two patient groups. However, suicide mortality has been reported to be high in individuals with opioid or amphetamine use disorders, 54 , 55 and mental health professionals should address psychological distress.…”
Section: Discussionmentioning
confidence: 99%